"Affluent and Tender Online": Instagramming Celebrity, Masculinity, and Fatherhood in Contemporary Greece. Issue 1 (March 2023) - Zestanakis, Panagiotis
This article explores the online construction of masculinity and fatherhood in contemporary Greece. Through a digital observation of five celebrities' Instagram activities that identified with the image of family man and affectionate father, the article argues that self-representations of affluent and involved masculinity and fatherhood represent a popular media trend. The article analyzes such self-representations as the outcome of historical transformations in gender and family politics, economy, and media that go back to the 1980s, the 1990s and the 2000s. It also argues that the acceptance of such imagery by wide audiences demonstrates the persistence of the male archetype of breadwinner, the value of the family, and the nostalgic survival of elements of earlier prosperous consumer aesthetics throughout the Greek economic crisis of the 2010s.